Disinformative Remixing in Internet Memes - Melo, Thiago Ramos de (2023)
The present study aims to analyze remixing strategies in internet memes serving disinformation, which we term disinformative remixing. In the contemporary digital landscape, where remix has become the driving force behind sociocultural processes (Lemos, 2006), we assume that understanding remixing strategies (Navas, 2019) in memes becomes a crucial tool in combating disinformation, considering that informational disorder flows (Wardle, 2017, 2020) largely traverse these techno-digital artifacts. In addition to the theoretical reflection guiding this work, for illustrative purposes, we propose the analysis of an internet meme in light of some analytical steps of Critical Discourse Analysis (CDA), following Fairclough (2001, 2003) and Chouliaraki and Fairclough (1999), along with the methodological procedures described by Navas (2019). Ultimately, we infer that analyzing the processes and effects caused by the influence of internet memes and understanding their 'memetic engineering' can become a crucial component in revising practices to combat disinformation in the contemporary digital landscape.